Quality of Demersal Fish sold at Tobelo Traditional Market, North Halmahera based on pH and Organoleptic Values - Akerina, Febrina Olivia; Kour, Femsy; Hibata, Yutita L. N. (Jurnal Ilmiah Platax, 2024)
Demersal fish resources are a type of fish whose life cycle is mostly at the bottom or around the bottom of the waters. Fishery products are food commodities that quickly spoil (deteriorate in quality) because they are influenced by the high water and nutrient content. Fish bodies are a good medium for the growth of putrefactive bacteria. Factors that influence the speed of reduction in fish freshness level are storage temperature. The application of cold chains is one way of handling that is easy to apply. This study aims to analyze the quality of demersal fish sold in one of the traditional markets in the city of Tobelo based on organoleptic and pH. The results of the analysis show that the organoleptic tests of gills, eyes, flesh, smell, and texture of fish meet the requirements of the Indonesian National Standard. The pH value of fish ranges from 6.00 - 6.65 which means fish are still in very good condition. Keywords: Demersal fish, organoleptic, pH, Tobelo Abstrak Sumberdaya ikan demersal merupakan jenis-jenis ikan yang siklus hidupnya sebagian besar berada di dasar atau sekitar dasar perairan. Hasil perikanan adalah komoditas pangan yang cepat mengalami pembusukan (kemunduran mutu) karena dipengaruhi oleh tingginya kandungan air dan nutrisi. Tubuh ikan merupakan media yang baik untuk pertumbuhan bakteri pembusuk. Faktor-faktor yang berpengaruh terhadap kecepatan penurunan tingkat kesegaran ikan adalah suhu penyimpanan. Penerapan rantai dingin merupakan salah satu cara penanganan yang mudah diterapkan. Penelitian ini bertujuan untuk menganalisis kualitas ikan demersal yang dijual di salah satu pasar tradisional di Kota Tobelo berdasarkan organoleptic dan pH. Hasil analisis menunjukkan bahwa Uji organoleptic insang, mata, daging, bau dan tekstur ikan memenuhi persyaratan Standar Nasional Indonesia. Nilai pH ikan berkisar dari 6,00 – 6,65 yang berarti ikan masih dalam kondisi sangat baik. Kata kunci : Ikan demersal, organoleptic, pH, Tobelo.